Interleukin-1β More Than Mechanical Loading Induces a Degenerative Phenotype in Human Annulus Fibrosus Cells, Partially Impaired by Anti-Proteolytic Activity of Mesenchymal Stem Cell Secretome - Gonçalves, Raquel M.; Saggese, Taryn; Yong, Zhiyao; Ferreira, Joana R.; Ignatius, Anita; Wilke, Hans-Joachim; Neidlinger-Wilke, Cornelia; Teixeira, Graciosa Q. (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stem/stromal cell (MSC)-based therapies for low back pain and intervertebral disc (IVD) degeneration have been emerging, despite the poor knowledge on their full mechanism of action. As failure of the annulus fibrosus (AF) is often associated with IVD herniation and inflammation, the objective of the present study was to investigate the impact of MSC secretome on human AF cells exposed to mechanical loading and a pro-inflammatory environment. Human AF cells isolated from IVD biopsies from patients with adolescent idiopathic scoliosis (AIS) or disc degeneration (DD) were exposed to physiological cyclic tensile strain (CTS) for 72 h in a custom-made device, with or without interleukin (IL)-1β medium supplementation. AF cells stimulated with CTS+IL-1β were then treated with secretome from IL-1β-pre-conditioned MSCs for 48 h. AF cells metabolic activity, gene expression, protein secretion, matrix metalloproteinases (MMPs) activity and tissue-inhibitors of MMPs (TIMPs) concentration were evaluated. Expanded AF cells from AIS and DD patients revealed similar metabolic activity and gene expression profile. CTS stimulation up-regulated collagen type I (COL1A1) expression, while IL-1β significantly stimulated IL-6, IL-8, MMP-1, MMP-3 gene expression and prostaglandin E2 production by AF cells, but down-regulated COL1A1. The combination of CTS+IL-1β had a similar outcome as IL-1β alone, accompanied by a significant up-regulation of elastin. The MSC secretome did not shown any immunomodulatory effect on CTS+IL-1β-stimulated AF cells, but significantly decreased MMP-1, MMP-2, MMP-3 and MMP-9, while increasing TIMP-1 an TIMP-2 production. The results obtained demonstrate a stronger impact of the inflammatory milieu on human AF cells than upper-physiologic mechanical stress. In addition, a new MSC mechanism of action in degenerated IVD consisting in the modulation of AF MMPs activity was evidenced. Together, the results obtained contribute to advance the knowledge in AF tissue weakening and IVD herniation.